Calcium Signalling in Neurological Disorders, with Insights from Miniature Fluorescence Microscopy - Dechuan Sun; Mona Amiri; Qi Meng; Ranjith R. Unnithan; Chris French (Cells)
Neurological disorders (NDs), such as amyotrophic lateral sclerosis (ALS), Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and schizophrenia, represent a complex and multifaceted health challenge that affects millions of people around the world. Growing evidence suggests that disrupted neuronal calcium signalling contributes to the pathophysiology of NDs. Additionally, calcium functions as a ubiquitous second messenger involved in diverse cellular processes, from synaptic activity to intercellular communication, making it a potential therapeutic target. Recently, the development of the miniature fluorescence microscope (miniscope) enabled simultaneous recording of the spatiotemporal calcium activity from large neuronal ensembles in unrestrained animals, providing a novel method for studying NDs. In this review, we discuss the abnormalities observed in calcium signalling and its potential as a therapeutic target for NDs. Additionally, we highlight recent studies that utilise miniscope technology to investigate the alterations in calcium dynamics associated with NDs.